Enhancing Active Learning Skills of Software Engineering Students: An Evaluation Using the SERVQUAL Model - Yi, Wenlong; Huang, Xuan; Luo, Yun (Computer Tools in Education, 2023)
In light of the contemporary landscape characterized by the swift advancement of novel technologies and the escalating societal demands for software professionals, this study endeavors to enhance students’ proactive learning capabilities to align with societal requisites. To achieve this objective, the study employs the service quality (SERVQUAL) model to assess and scrutinize the pivotal factors that contribute to the enhancement of students’ self-directed proficiencies, thereby refining and augmenting the higher education system. The SERVQUAL model was employed to construct a questionnaire, with a specific focus on surveying students enrolled in software major and related disciplines. By conducting data analysis and employing weighting operations on the survey findings, a comparison and evaluation were conducted on the disparities in students’ perceptions and expectations regarding service quality. The outcomes indicate a fundamental alignment between students’ perceptions and expectations concerning the enhancement of active learning capabilities, thereby affirming the overall commendable service quality. These findings further suggest that the teaching standards of the major and the students’ active learning abilities have successfully fulfilled the anticipated criteria.